Estudo da viabilidade de adição de resíduo de pó de fumo à massa cerâmica - Lopes, Diorges Carlos (2005)
This research comprehends the study of the viability of adding residues from the tobacco industry (tobacco dust) in the ceramics mass for the production of pottery. It aims the incorporation of this residue in the mixture (with proper destination) as a partial substitute of the main substance (clay economy). For this research it has been used three samples of argillaceous ground from hillfield and a sample of residues from the tobacco industry. The argillaceous ground samples (raw materials) were prepared and characterized according to the ABNT techniques and a number of testing mouldings were produced according to the procedures recommended by the Fundação de Ciência e Tecnologia of the Rio Grande do Sul State - CIENTEC. The residue was added to the ceramic mass with percentages of 5, 10, 15, and 20% of the volume of clay in dust form, as collected in the industry, also in the same percentages the addition of the tobacco dust ash was studied. The analysis of the results indicates the viability of the use of the additions of ash or residue in the manufacture of massive bricks, blocks and roofing tiles. The chemical analysis of the residue and ash samples, and the leaching assays made with a moulding sample with 15% of residue added plus another one with 10%, both indicate values in accordance to bands of acceptance indicated by the NBR 10004.